Use of fatty acids in the chemotaxonomy of the family Selenastraceae (Sphaeropleales, Chlorophyceae). (July 2018) - Mori, Cilene Cristina; Bagatini, Inessa Lacativa; Garcia da Silva, Thais; Parrish, Christopher Charles; Henriques Vieira, Armando Augusto
Abstract: The family Selenastraceae includes many species of freshwater green microalgae with morphological characteristics that are so subtly different that it is difficult to discriminate species within it. Therefore, the use of the diacritical characteristics of traditional morphological taxonomy may be ineffective at differentiating among many species of the family. Chemotaxonomy based on fatty acid methyl ester (FAME) can help resolve uncertainties not completely addressed by other approaches, such as molecular studies of some species within the Selenastraceae. Here, we first tested three techniques for the analysis of microalgal FAME to choose the one that would provide the best profiles for chemotaxonomy: 1) direct transesterification (DT) of the biomass followed by gas chromatography coupled to mass spectrometry analysis (GC-MS); 2) extraction using chloroform and methanol, followed by transesterification (T) and then analysis by gas chromatography/flame ionization detector (GC-FID); and 3) extraction with chloroform and methanol and then separation into lipid classes using thin-layer chromatography (TLC) using the Iatroscan-Chromarod system. The tests were conducted on 12 strains (11 species) of Selenastraceae and one outgroup strain. The fatty acid profiles produced by the DT-GC-MS technique yielded the best results for the chemotaxonomy of the Selenastraceae species using 12 FAME. The proportion of the variance in the fatty acid profiles obtained with DT-GC-MS analysis explained by species was 85%, whereas the differences explained by strains was 92%. Therefore, DT-GC-MS was used to analyze other microalgae strains, totaling 15 species of 8 genera of green coccoid microalgae, including the recently described Curvastrum . The results with all strains showed that fatty acid profiles obtained by DT-GC-MS were significantly different (p < 0.001) among strains and among species. The variance in fatty acids profiles explained by separation into strains was 97%, whereas the separation into species explained 93% of the variance. Statistical analyses showed that, for our dataset, the C18 fatty acids 18:3ω3 and 18:4ω6 were indicative of the Selenastraceae. Therefore, fatty acid profiles are a useful auxiliary chemotaxonomic tool for species identification in Selenastraceae. Graphical abstract: Highlights: The TD-GC-MS method was more effective to discriminate taxa than other tested methods. Axenic cultivation is an essential condition for success in taxa discrimination. Some of the fatty acids are biomarkers for genera and/or species. The high specific diversity of fatty acids indicates its usefulness in taxonomy.